B Chromosomes – A Matter of Chromosome Drive - Houben, Andreas (Frontiers in Plant Science, 2017)
B chromosomes are supernumerary chromosomes which are often preferentially inherited, deviating from usual Mendelian segregation. The balance between the so-called chromosome drive and the negative effects that the presence of Bs applies on the fitness of their host determines the frequency of Bs in a particular population. Drive is the key for understanding most B chromosomes. Drive occurs in many ways at pre-meiotic, meiotic or post-meiotic divisions, but the molecular mechanism remains unclear. The cellular mechanism of drive is reviewed based on the findings obtained for the B chromosomes of rye, maize and other species. How novel analytical tools will expand our ability to uncover the biology of B chromosome drive is discussed.